Organized crime and foreign direct investment: the Italian case - Vittorio Daniele; Ugo Marani (Center for Economic Studies and ifo Institute (CESifo), 2008)
The objective of this paper is to examine the impact of crime on FDI inflows in 103 Italian provinces. The incidence of criminality is measured through the number of complaints for different kinds of crime. The analysis has been conducted using different estimation methods for panel data. The results show how the correlation between organized crime is both negative and significant. This relationship appears strong even when, in specifications, it is considered as an indicator of financial incentives for investment. Furthermore, such a correlation between crime and FDI seems to be valid only for certain crimes, traditionally related to the presence of Organized crime of the mafia type. Even if these results suggest that crime is, in itself, a deterrent for foreign investors, this does not exclude the possibility that a high incidence of (certain) crimes may be perceived as a signal of a socio-institutional environment unfavourable for FDI.
Keywords: F23; R30; R38; 330; FDI determinants; Italy; Mezzogiorno; crime; regional attractiveness; Kriminalität; Region; Provinz; Standortfaktor; Direktinvestition; Ausländisch; Italien